Analysis of future water demands in Al-Madinah (1990–2030) based on the modified IPAT model and sheared socio-economic pathways scenarios - Ohood Alharbi; Marco Sakai; Colin McClean (Sustainable Water Resources Management, 2024)
Arid regions such as Saudi Arabia are facing water scarcity and availability issues and experiencing growing pressure by rapid water consumption. Determining the main driving forces contributing to rising water demands and future water demand prediction are considered the cornerstone for developing a good sustainable management plan. Al-Madinah city was chosen as a case study. In this study, the population, affluence, and technology (IPAT) model has been modified to apply in the water sector to analyse water needs in Al-Madinah from 1990 to 2020 and examines factors including population, GDP-per capita, agricultural lands/GDP and built-up area/agricultural lands. In addition, Sheared Socio-economic Scenarios (SSPs) have been developed to predict water demands in Al-Madinah from 2020 to 2030. The results confirm that population was the most important in explaining water consumption trends. Moreover, water demand under all IPCC_ SSP scenarios is expected to increase by between 17 to 28%. The scenarios of SSP3 and SSP4 are projected to experience an increase in water demands by an average of 25% and 26%, respectively. In contrast, the water demand is forecasted to lower under the SSP1 and SSP5 by around 20% and 17%, respectively. This evaluation could highly reinforce and improve sustainable water resource management strategies, which have recently become increasingly essential to face growing water challenges and demands.

When Space and Time Matter in Environmental Injustice: A Bayesian Analysis of the Association between Socio-economic Disadvantage and Air Pollution in Greater Mexico City - Alejandro Lome-Hurtado; Julia Touza; Piran C. L. White; Colin J. McClean (Environmental Management, 2024)

Smallholder perceptions of land restoration activities: rewetting tropical peatland oil palm areas in Sumatra, Indonesia - Caroline Ward; Lindsay C. Stringer; Eleanor Warren-Thomas; Fahmuddin Agus; Merry Crowson; Keith Hamer; Bambang Hariyadi; Winda D. Kartika; Jennifer Lucey; Colin McClean; Neneng L. Nurida; Nathalie Petorelli; et al. (Regional Environmental Change, 2021)
The Indonesian government committed to restoring over 2 million ha of degraded peatland by the end of 2020, mainly to reduce peat fires and greenhouse gas emissions. Although it is unlikely the government will meet this target, restoration projects are still underway. One restoration strategy involves blocking peatland drainage canals, but the consequences of this for smallholder farmers whose livelihoods are dependent on agriculture are unclear. This paper investigates perceived impacts of canal blocks on smallholder farmers and identifies factors that affect their willingness to accept canal blocks on their land. We use data from 181 household questionnaires collected in 2018 across three villages in Jambi province, Sumatra. We found that the majority of respondents would accept canal blocks on their farms, perceiving that the blocks would have no impact on yields or farm access, and would decrease fire risk. Respondents who would not accept blocks on their farms were more likely to use canals to access their farms and perceive that canal blocks would decrease yields. The majority of farmers unwilling to accept canal blocks did not change their mind when provided with an option of a block that would allow boat travel. Our results improve understanding of why some smallholders may be unwilling to engage with peatland restoration. Further research is needed to understand the impact of canal blocks on smallholders’ yields. Engaging with stakeholders from the outset to understand farmers’ concerns, and perceptions is key if the government is to succeed in meeting its peatland restoration target and to ensure that the costs and benefits of restoration are evenly shared between local stakeholders and other actors.

Evidence gaps and biodiversity threats facing the marine environment of the United Kingdom’s Overseas Territories - Bethan C. O’Leary; Philip Fieldhouse; Colin J. McClean; Adriana E. S. Ford; Polly Burns; Julie P. Hawkins; Callum M. Roberts (Biodiversity and Conservation, 2019)

A critical re-evaluation of controls on spatial and seasonal variations in nitrate concentrations in river waters throughout the River Derwent catchment in North Yorkshire, UK - Shaheen Begum; Muhammad Adnan; Colin J. McClean; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2016)

Protected areas of Borneo fail to protect forest landscapes with high habitat connectivity - Sarah Proctor; Colin J. McClean; Jane K. Hill (Biodiversity and Conservation, 2011)

Atmospheric nitrogen deposition explains patterns of plant species loss - COLIN J. McCLEAN; LEON J. L. van den BERG; MIKE R. ASHMORE; CHRIS D. PRESTON (Global Change Biology, 2011)
Atmospheric nitrogen ( N ) deposition across Europe increased substantially from the 1950s to the 1990s. Targeted surveys suggest a negative correlation between N deposition and species richness within quadrats in sensitive habitats. However, it remains unclear whether plant species losses at national recording scales are correlated with nitrogen deposition. We relate plant species losses before 1987 in Great Britain to reduced and oxidized N deposition, land use change and climate change. The mean Ellenberg fertility ( N ) indices of plant species lost in each 100 km 2 cell before 1987 was compared with those of species that were recorded between 1987 and 1999. In 45% of squares, indices of species lost were significantly lower than those for species present after 1986. For 17%, primarily upland, squares, the opposite effect was found. A generalized least squares regression model, with difference in the mean Ellenberg N index between samples as the dependent variable, showed that higher deposition of reduced N was significantly associated with selective loss of species with a lower index. Arable land use and change in arable land use also demonstrated this positive relationship. Rough grazing, change in rough grazing, change in pasture and change in annual precipitation showed negative effects. Difference in Ellenberg R index was highly correlated with difference in Ellenberg N and was negatively correlated with oxidized N deposition, suggesting that the lack of a significant effect of oxidized N deposition on Ellenberg N was because it had effects through both acidification and eutrophication, while the effect of reduced N deposition was primarily through eutrophication. Our results suggest that N deposition, along with land use and precipitation changes, has been a significant driver of local plant extinctions. With N deposition increasing in many parts of the world, local extinctions of plant species may be experienced in other regions.

Model‐based uncertainty in species range prediction - Richard G. Pearson; Wilfried Thuiller; Miguel B. Araújo; Enrique Martinez‐Meyer; Lluís Brotons; Colin McClean; Lera Miles; Pedro Segurado; Terence P. Dawson; David C. Lees (Journal of Biogeography, 2006)
Aim Many attempts to predict the potential range of species rely on environmental niche (or ‘bioclimate envelope’) modelling, yet the effects of using different niche‐based methodologies require further investigation. Here we investigate the impact that the choice of model can have on predictions, identify key reasons why model output may differ and discuss the implications that model uncertainty has for policy‐guiding applications. Location The Western Cape of South Africa. Methods We applied nine of the most widely used modelling techniques to model potential distributions under current and predicted future climate for four species (including two subspecies) of Proteaceae. Each model was built using an identical set of five input variables and distribution data for 3996 sampled sites. We compare model predictions by testing agreement between observed and simulated distributions for the present day (using the area under the receiver operating characteristic curve (AUC) and kappa statistics) and by assessing consistency in predictions of range size changes under future climate (using cluster analysis). Results Our analyses show significant differences between predictions from different models, with predicted changes in range size by 2030 differing in both magnitude and direction (e.g. from 92% loss to 322% gain). We explain differences with reference to two characteristics of the modelling techniques: data input requirements (presence/absence vs. presence‐only approaches) and assumptions made by each algorithm when extrapolating beyond the range of data used to build the model. The effects of these factors should be carefully considered when using this modelling approach to predict species ranges. Main conclusions We highlight an important source of uncertainty in assessments of the impacts of climate change on biodiversity and emphasize that model predictions should be interpreted in policy‐guiding applications along with a full appreciation of uncertainty.

Major gaps in the distribution of protected areas for threatened and narrow range Afrotropical plants - Neil Burgess; Wolfgang KÜper; Jens Mutke; Joanna Brown; Sally Westaway; Susie Turpie; Charles Meshack; James Taplin; Colin McClean; Jon C. Lovett (Biodiversity and Conservation, 2005)